Reformation and the German territorial state: Upper Franconia, 1300 - 1630 - Smith, William Bradford (Changing perspectives on early modern Europe, 2008)
Territory and community -- Rebellion, representation, and reform -- "Lord in our own house" -- Reformation and revolution -- The limits of obedience -- A plague of preachers -- Orthodoxy and order -- The Christian commune -- Cuius regio? -- The stool of wickedness